PEMAHAMAN MATERI PEMBELAJARAN MELALUI DARING BAGI WARGA BELAJAR PADA PKBM AR RUHAMA KELURAHAN LEMBAH DAMAI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Dila Oktavia; Said Suhil Achmad; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe the understanding of online learningmaterials for learning residents at PKBM Ar Ruhama, Lembah Damai Village, RumbaiPesisir District, Pekanbaru City. In understanding learning material through online forlearning citizens, it includes the behavior of explaining again, giving examples,summarizing the material, and concluding the material. This type of research isdescriptive with a qualitative approach, aiming to describe the behavior under study.The data collection process was carried out by observation, interviewing 6 subjects,namely control informants, core informants 1, core informants 2, core informants 3,core informants 4, core informants 5 with documentation included. Based on the resultsof the interviews, the researchers found 4 indicators, namely: (1) Explaining again, (2)Giving examples, (3) Summarizing the material, (4) Summarizing the material. Thestudy of the 4 indicators is very useful to find out how to understand online learningmaterials for learning residents at PKBM Ar Ruhama, Lembah Damai Village, RumbaiPesisir District, Pekanbaru City.Key Words: Material Understanding, Online Learning, Learning Citizens